Beyond climate change attribution in conservation and ecological research. (16th May 2013) - Parmesan, Camille; Burrows, Michael T.; Duarte, Carlos M.; Poloczanska, Elvira S.; Richardson, Anthony J.; Schoeman, David S.; Singer, Michael C.
Abstract: There is increasing pressure from policymakers for ecologists to generate more detailed 'attribution' analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change (ACC), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ' very high confidence' [ sensu Intergovernmental Panel on Climate Change (IPCC)] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.